PENERAPAN KONTRAK ELEKTRONIK DALAM BISNIS DIGITAL - Jamba, Padrisan; Husna, Lenny; Ukas, Ukas (JURSIMA, 2025)
The implementation of electronic contracts in digital business has become one of the significant developments in the era of rapid information technology. Electronic contracts enable more efficient, faster, and flexible business transactions by utilizing electronic media, such as computers and the internet. These contracts offer several advantages, including facilitating cross-border business interactions, reducing reliance on physical documents, and speeding up administrative processes. However, the adoption of electronic contracts also faces various legal challenges that need to be addressed, such as issues related to contract validity, authentication of the parties involved, and the protection of personal data and information security. Additionally, legal ambiguities surrounding electronic contracts in some jurisdictions remain a barrier, given the differences in existing regulations. Therefore, it is essential to develop clear and comprehensive regulations regarding electronic contracts, which can provide adequate legal protection for all parties involved in digital business transactions. The legal framework governing the implementation of electronic contracts should take into account technology, transparency, and the validity of transactions to create a safe and trustworthy digital business environment. This study aims to examine the legal aspects of the implementation of electronic contracts in digital business and the challenges that arise in their implementation.